2008
DOI: 10.1039/b802036a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive detection of bacterial toxin with silicon nanowire transistor

Abstract: Nanowire field effect transistors (nano-FET) were lithographically fabricated using 50 nm doped polysilicon nanowires attached to two small gold terminals separated from each other by a approximately 150 nm gap to serve as the basis for electronic detection of bacteria toxins. The device characterizations, semiconducting properties and use in a robust and sensitive bio-molecular detection sensor of bacterial toxins were reported in this work. The device characteristics were demonstrated with varying gate and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…One first explanation could be a transfer of charges (electrons) of the bacteria into the nanowires which fill the traps previously mentioned, and thus could and contribute to the decrease of the electrical resistivity of the nanowires [23]. Another possible reason is that the electrically charged bacteria may behave as biological gate resulting as wellknown field effect [13][14][15]17] on the SiNWs. At last, other explanation is that bacteria may act as additional conducting paths randomly distributed between teeth thanks to hooking effect of bacteria into the SiNWs network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One first explanation could be a transfer of charges (electrons) of the bacteria into the nanowires which fill the traps previously mentioned, and thus could and contribute to the decrease of the electrical resistivity of the nanowires [23]. Another possible reason is that the electrically charged bacteria may behave as biological gate resulting as wellknown field effect [13][14][15]17] on the SiNWs. At last, other explanation is that bacteria may act as additional conducting paths randomly distributed between teeth thanks to hooking effect of bacteria into the SiNWs network.…”
Section: Resultsmentioning
confidence: 99%
“…In this case nanowires act as sensing elements. However, few works report on SiNWs use as great promising method for label free, ultra-sensitive and real-time detection of bacteria [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The use of silicon nanowires (SiNW) as the sensitive element of such sensor systems was firstly demonstrated by Lieber and coworkers (15). It has been shown that the devices can be very versatile to detect biomolecules such as DNA (14)(15)(16)(17), proteins (15), antibodies or antigens (18), bacterial toxins (19), virus (20,21), cell secretes (22), cardiac markers (23), and electrical activity of cardiac cells (24)(25)(26) as well as of neurons (27).…”
Section: Introductionmentioning
confidence: 99%
“…Some electrochemical devices which are imunosensors along with cerium oxide nanoparticles and chitosan nanocomposites using nanowire based transistors and carbon nanotubes which detect several toxins like staphylococcal enterotoxin [21] and cholera toxin [22]. These detector systems at nano level have an advantage that they are able to detect impurities, pollutants and toxic chemicals in very low quantity even at nanolevel [23].…”
Section: Detection Of Chemicalsmentioning
confidence: 99%